Hyalinising clear cell carcinoma of salivary gland: a case report - Osuchowski, Michał; Bartusik-Aebisher, Dorota; Kaznowska, Ewa; Aebisher, David (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Clear cell carcinoma, not otherwise specified/hyalinising clear cell carcinoma of the salivary gland (HCCC) is a malignancy that arises in minor salivary glands. It rarely leads to distant metastases or cancer-related death but has the potential for recurrence and focal metastases. Aim. A case is reported. Description of the case. A 72 years old female patient has reported to the Clinic of Otolaryngology with a tongue lesion. The patient had no history of malignancy. The lymph node has been surgically removed for further examination. Cords and nests of clear cells and cells with eosinophilic cytoplasm in a hyalinized stroma were identified within the lymph node. After the diagnosis the patient has been transferred to another Oncology Hospital for further treatment. Conclusion. The diagnosis of clear cell carcinoma may be challenging because many of it‘s features frequently overlap with other salivary gland lesions.
Keywords: cancer; hyalinising clear cell carcinoma; salivary gland